Working to learn: transforming learning in the workplace - Evans, Karen; Hodkinson, Phil; Unwin, Lorna (Northants Routledge, 2002)
The workplace is an important site for learning in today's society. This book examines the changing nature of the work and effect that this has on the skill and knowledge requirements of individuals, its implications for employment, and ways in which these changing requirements can be met.
Age Group: Adult
Keywords: (ETB-2007) Travel and Tourism Work Placement